RHAMM Alters Vascular Smooth Muscle Cell Constrictive Matrix Remodeling - MA, XUE (Wake Forest University, 2012)
Restenosis, which is defined as a new lumen narrowing at the site of previous vascular reconstruction, affects millions of patients each year worldwide. Restenosis has been a major limitation of surgical and endovascular reconstructions since their inception and while decades of research have yielded improved results for percutaneous coronary interventions (PCI), strategies to eliminate restenosis remain elusive. Also, increased application of endovascular therapy to extra-coronary vascular beds has been met with very high rates of late failures. Intimal hyperplasia and constrictive remodeling are the two primary structural mechanisms that lead to restenosis. Constrictive remodeling refers to artery wall shrinkage independent of new wall mass formation after arterial intervention. The purpose of the studies described in this dissertation was to determine whether smooth muscle cell (SMC) interactions with hyaluronan (HA) mediated by the receptor for hyaluronan-mediated motility (RHAMM), affects arterial SMC adhesion, migration and collagen matrix remodeling in vitro as well as constrictive remodeling following artery injury in vivo.
Keywords: Constrictive remodeling; Hyaluronan; Restenosis; RHAMM; Smooth muscle cell